2020
DOI: 10.1017/prp.2020.1
|View full text |Cite|
|
Sign up to set email alerts
|

Meditation effect in changing functional integrations across large-scale brain networks: Preliminary evidence from a meta-analysis of seed-based functional connectivity

Abstract: Meditation is a type of mental training commonly applied in clinical settings and also practiced for general well-being. Brain functional connectivity (FC) patterns associated with meditation have revealed its brain mechanisms. However, the variety of FC methods applied has made it difficult to identify brain communication patterns associated with meditation. Here we carried out a coordinate-based meta-analysis to get preliminary evidence of meditation effects on changing brain network interactions. Fourteen s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 117 publications
(160 reference statements)
0
5
0
Order By: Relevance
“…It is unknown how long-term meditation practice might impact claustrum functioning in relation to the DMN/FPN compared with the general population. However, it has previously been shown that intensive mediation training can significantly alter DMN functional connectivity (Shen et al, 2020) and produces increases in between DMN and salience network functional connectivity (Vishnubhotla et al, 2021). Regions within the salience network in fMRI studies often include parts of the claustrum (Krimmel et al, 2019), as it is adjacent to the insula, which is a node of the salience network (Menon, 2011).…”
Section: The Claustrum: Worth Further Explorationmentioning
confidence: 99%
“…It is unknown how long-term meditation practice might impact claustrum functioning in relation to the DMN/FPN compared with the general population. However, it has previously been shown that intensive mediation training can significantly alter DMN functional connectivity (Shen et al, 2020) and produces increases in between DMN and salience network functional connectivity (Vishnubhotla et al, 2021). Regions within the salience network in fMRI studies often include parts of the claustrum (Krimmel et al, 2019), as it is adjacent to the insula, which is a node of the salience network (Menon, 2011).…”
Section: The Claustrum: Worth Further Explorationmentioning
confidence: 99%
“…after training using fMRI 85,86,96 . Additionally, such training has been linked with changes in PCC-DLPFC connectivity [97][98][99] . In fact, many studies now show that inter-network connectivity between the FPN, CON and DMN are altered after meditative/ mindfulness training [100][101][102][103][104][105] .…”
Section: Discussionmentioning
confidence: 99%
“…To restate, CT directs EFL students in their assessments of the value of the university and their sense of belonging there, as well as in their convictions regarding the efficacy of their language classes. Students are highly encouraged to actively participate in class debates and other speaking exercises, since they are an essential component of any language education [ 15 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…CFA is a statistical method used to validate the component structure of a given collection of observed data. Additionally, CFA enables researchers to examine if there is a connection between observable variables and the latent constructs that underlie them [ 56 , 57 ].…”
Section: Methodsmentioning
confidence: 99%